PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINKPAIR-SHARE UNTUK MENINGKATKAN PEMAHAMAN KONSEP MASALAH SOSIAL IPS PADA SISWA SEKOLAH DASAR - Candra Dewi (Universitas PGRI Madiun, 2015)
The purpose of this research is: to improve understanding of social problem concept ofsocial studies through applying cooperative learning model type think-pair-share in thestudents of Elementary School. This is classroom action research (CAR) with two cyclesperformed. Each cycles consist of four steps, there were planning, implementation ofaction, observation and reflection. The subjects of this research is fourth grade studentsin Elementary School State 2 Kedungputeri Ngawi. Data collecting techniques in thisresearch was observation, test, interview and documentation. For data analyzingtechniques was reducing data, presenting data, and taking research conclusion orverification. The research result can be conclude that there is an improvementunderstanding of social problem concept of social studies in fourth grade students ofElementary School State 2 Kedungputeri Ngawi. On initial conditions, the class averagevalue is 61,31 by the number of students who complete learned is 11 students (40,74%).In cycle I, the average value is 79,51 with students who complete learned is 22 students(81,48%). In cycle II, the average value is 91,26 with students who complete learned is 25students (92,59%).